Co-Blogging Law - Eric Goldman (Washington University Law Review, 2006)
Bloggers often work collaboratively with other bloggers, a phenomenon I call “co-blogging.” The decision to co-blog may seem casual, but it can have significant and unexpected legal consequences for the co-bloggers. This Article looks at some of these consequences under partnership law, employment law, and copyright law and explains how each of these legal doctrines can lead to counterintuitive results. The Article then discusses some recommendations to mitigate the harshness of these results.
Keywords: Blogs; United States; Partnership; Employment; Copyright